Hippocampus: seahorse; brain-structure; spatial map; concept - Armstrong, Beth Diane (Rhodes University, Faculty of Humanities, Department of Fine Art, 2010)
Through an exploration of both sculptural and thought processes undertaken in making my Masters exhibition, 'Hippocampus', I unpack some possibilities, instabilities, and limitations inherent in representation and visual perception. This thesis explores the Hippocampus as image (seahorse) and concept (brain-structure involved in cognitive mapping of space). Looking at Gilles Deleuze's writings on representation, I will expand on the notion of the map as being that which does not define and fix a structure or meaning, but rather is open, extendable and experimental. I explore the becoming, rather than the being, of image and concept. The emphasis here is on process, non-representation, and fluidity of meaning. This is supportive of my personal affirmation of the practice and process of art-making as research. I will refer to the graphic prints of Maurits Cornelis Escher as a means to elucidate a visual contextualization of my practical work, particularly with regard to the play with two- and three-dimensional space perception. Through precisely calculated 'experiments' that show up the partiality of our visual perception of space, Escher alludes to things that either cannot actually exist as spatial objects or do exist, but resist representation. Similarly I will explore how my own sculptures, although existing in space resist a fixed representation and suggest ideas of other spaces, non-spaces; an in-between space that does not pin itself down and become fixed to any particular image, idea, objector representation.
Keywords: Hippocampus (Brain); Sea horses -- Symbolic representation; Meaning (Philosophy); Deleuze, Gilles, 1925-1995; Escher, M C (Maurits Cornelis), 1898-1972; Visual perception; Space perception; Optical art; Art -- Themes, motives